2013
DOI: 10.1080/00103624.2013.803562
|View full text |Cite
|
Sign up to set email alerts
|

Balanced Fertilization along with Farmyard Manures Enhances Abundance of Microbial Groups and Their Resistance and Resilience against Heat Stress in a Semi-arid Inceptisol

Abstract: The impact of long-term (36-year) application of balanced fertilizers and farmyard manures (FYM) on the abundance of microbial groups (bacteria, fungi, actinomycetes, Pseudomonas, Azotobacter, ammonia-oxidizing bacteria) and their resistance and resilience against heat stress was investigated in a semi-arid Inceptisol at New Delhi, India. Surface soils from selected treatments [control, nitrogen (N), N and phosphorus (P), NP and potassium (K), NPK + FYM] under a maize crop were assessed immediately after sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…, Kumar et al. ). In addition, the higher OM content in these soils probably buffered the impact of the heat stress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, Kumar et al. ). In addition, the higher OM content in these soils probably buffered the impact of the heat stress.…”
Section: Resultsmentioning
confidence: 99%
“…More details of the rational of adopting this approach for quantification of resistance and resilience are given elsewhere (Kumar et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…Lesser plant spacing also help in retaining moisture of soil for longer period, which provided optimal condition for soil microbial communities that helped in nutrient transformation and ultimately improved nutrient supplying capacity of soil as also advocated by Kumar et al, (2013).…”
Section: Resultsmentioning
confidence: 99%
“…Integration of FYM with inorganic fertilizers significantly enhanced bacterial, fungal, ACT and PSM (Kumar et al, 2013). Yevdokimov et al (2008) found that addition of increasing amounts of N fertilizers increased soil fungal biomass significantly.…”
Section: Microbial Counts and Enzymatic Activitymentioning
confidence: 98%